Reflection of Women’s Participation in Boards and Committees on the Quality of Profits: An Applied Study - Ibrahim, Nahla Mohamad El Sayed (The Arab Journal of Administration, 2024)
The study aimed to identify the reality of Saudi women’s participation in the board of directors and board committees in Saudi joint stock companies, and to identify the impact of women’s participation in the board of directors, the nominations and rewards committee, the audit committee, and the executive management on the quality of profits, by applying to a sample of 15 joint stock companies. In the Saudi Stock Exchange, during the period 2017-2018, the study found several descriptive indicators, the most important of which are: The percentage of women’s participation in the board of directors of companies in the Kingdom of Saudi Arabia is still weak, as the percentage of women’s participation in the board of directors of the companies under study ranged between zero and 22%, with an average arithmetic average of about 8%, and the percentage of women’s participation in the Nomination Committee for Companies in the Kingdom of Saudi Arabia is also still weak, but it is higher than the Board of Directors, where the average percentage of women’s participation in the Nomination Committee is approximately 10%, and the percentage of women’s participation in the Audit Committee Companies in the Kingdom of Saudi Arabia are also still weak, but it is less than participation in the Board of Directors and the Nomination and Remuneration Committee, where the average percentage of women’s participation in the Committee Nominations are approximately 7%, while the lowest percentage of women’s participation in the executive management of companies in the Kingdom of Saudi Arabia compared to the rest of the committees, where the average rate of women’s participation in the Executive Management Committee is approximately 5%. The results of the study’s hypotheses tests also revealed the following: There is a positive effect of women’s participation in (Board of Directors, Nominations and Rewards Committee, Executive Management) on the quality of profits, while there is no effect of women’s participation in the Audit Committee on the quality of profits, and the study recommended the need to pay attention to strengthening The participation of women in the administrative work of companies and spreading awareness in the community of the importance of empowering women in the field of work because of its positive impact on reducing earnings management practices.